A Simple Aptasensor Based on Fluorescence Resonance Energy Transfer for the Rapid Detection of Cadmium (II) In Water and Food - Zhu, Jiangxiong; Wang, Yang; Wang, Lumei; Geng, Xueqing; Yang, Linnan; Zhao, Ting; Deng, Yun (Current Analytical Chemistry, 2025)
ObjectiveThe objective of this study is to develop a novel fluorometric aptasensor employing fluorescence resonance energy transfer (FRET) for the detection of Cadmium (II) (Cd2+) in water and food samples. The constructed aptasensor employed a fluorophore-quencher labeled aptamer combination not previously reported for Cd2+ detection. Additionally, its simple mix-and-detect pattern without immobilization or material-assisted steps represented an innovative design.MethodsUtilizing 6-carboxyfluorescein (FAM)-modified aptamers and maleimide (BHQ-1)-modified aptamer complementary chain to construct a fluorescent detection probe, this aptasensor achieved a rapid, sensitive, and selective detection of Cd2+. Without Cd2+, the aptamer and its complementary strand undergo base pairing, bringing the FAM closer to the BHQ-1, and leading to FRET and a subsequent decrease in fluorescence intensity. The introduction of Cd2+ preferentially brought to the aptamer, changing its conformation and preventing the quenching of FAM by BHQ-1, thereby restoring the fluorescence intensity of the aptasensor.ResultsFollowing optimization of experimental parameters, the aptasensor exhibited a linear response to Cd2+ concentrations ranging from 5 to 1200 nM, with a detection limit (LOD) of 0.43 nM. The aptasensor’s performance was unaffected by the presence of various ions, indicating its high specificity. Moreover, it could rapidly and accurately detect Cd2+ in water and food samples, including tap water, lake water, grapes, cabbage, and broccoli, demonstrating its substantial potential for practical application.ConclusionTherefore, the developed aptasensor represents an important tool for effective Cd2+ detection in water and food matrices, highlighting its potential as a critical tool for environmental monitoring and food safety.
Keywords: Cadmium (II)